Role of autologous bone marrow derived stem cells and platelet rich plasma for endometrial regeneration and repair and ovarian rejuvenation - Anagani, Manjula; Agrawal, Prabha; Reddy, Bollavaram Vikas; Mishra, Prabhu Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Stem cells are undifferentiated cells with a potential for self- renewal and differentiation into multiple mature cell types. PRP is blood plasma that has been enriched with platelets and multiple growth factors that can stimulate cellular processes and activate multi-potent stem cells to generate new, younger tissue and new blood vessels relevant to ovarian rejuvenation and endometrial regeneration. Methods: This study was to evaluate the effectiveness of ABMDSC and PRP application in patients with thin endometrium refractory to treatment, premature ovarian failure, infertility and menopause. 37 symptomatic women between age group 18 years to 56 years were selected for ABMDSC and PRP instillation in endometrium and/ or ovaries. PRP was instilled in endometrium in 8 patients, in ovaries in 5 patients and in both endometrium and ovaries in 24 patients. Results: There was significant improvement in endometrial thickness, along with improved blood flow to both endometrium and ovaries. FSH levels decreased and ovarian volume increased. There were three confirmed pregnancies with one delivery. Menopausal symptoms decreased in 2 patients and spontaneous resumption of menses was seen in 1 patient of POF. Conclusions: Stem cell therapy serves as a game changer with their unique properties, offering solutions for scores of women suffering from POF, poor oocyte quality, endometrial degeneration/ damage or menopausal symptoms.